PENGARUH PEMAHAMAN ATAS MEKANISME PEMBAYARAN PAJAK, PENGETAHUAN PERPAJAKAN, KESADARAN MEMBAYAR PAJAK, DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM (Studi Pada UMKM di Kota Palangka Raya) - Perdi Sahat Maruli Sihaloho; Lamria Simamora; Rini Oktavia; Ec. Rapel; Golda Belladonna Umbing (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to determine the influence of Understanding Tax Payment Mechanisms, Tax Knowledge, Tax Awareness, and Tax Service Quality on Taxpayer Compliance of MSMEs in Palangka Raya City. This study uses primary data whose data collection uses a questionnaire. In this study, the researcher used quantitative analysis, multiple linear regression analysis and coefficient of determination analysis with the help of SPSS 25. The population in this study were 100 MSME taxpayers in Palangka Raya City. The results of the study obtained using the t-test show that understanding the tax payment mechanism does not affect taxpayer compliance, tax knowledge does not affect MSME taxpayer compliance, tax awareness has a positive effect on MSME taxpayer compliance and the quality of tax services does not affect MSME taxpayers.